Rural Health - Why and How - Sunil Kumar Raina; Raman Kumar (Wolters Kluwer Medknow Publications, 2024)
With access a major issue on the supply side of the supply- demand chain of health care, reaching out to the rural population is not only needed but also imperative as part of delivering comprehensive primary health care.